(untitled) (American Journal of Islam and Society, 1987)
Translation In the name of Allah, the most benevolent, ever merciful. God commands justice, the doing Of good, and liberality to kith And kin, and He forbids All shameful deeds, and injustice And rebellion: He instructs you, That ye may receive admonition. Surah 16:90 If we look at the above verses we can see that the goal and essence of man’s life on earth is to live and follow the right course of life. The essence of this life, on the positive side, is summarized in the first part of Surah 16:90 of the Qur’an. The ultimate is for man to attain a life of justice (’adl), sincerity, concern, compassion, responsibility, and perfection (Ihsan) . In addition, one should exhibit the attributes of generosity and self-sacrifice in rendering help to individuals and groups n every way and with regard to priorities (‘ita thawi al qurba). On the negative and protective side, man should condemn and refrain from committing or indulging in sinful, flagrant, tasteless, harmful deeds and actions (al Fahsha’ wa al-Munkar). Likewise he should avoid acts of injustice, usurpation, suppression or oppression against any person or rights of any human being (baghy). Recite what is sent Of the Book by inspiration To thee, and establish Regular Prayer: for Prayer Restrains from shameful And unjust deeds; And remembrance of God Is the greatest (thing in life) Without doubt. And God knows The (deeds) that ye do. Surah 29:45 ...